2021
DOI: 10.1111/bjet.13151
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' digital competence to assist students with functional diversity: Identification of factors through logistic regression methods

Abstract: We are experiencing a serious health crisis due to COVID‐19 that has a major impact on the field of education. The educational system therefore needs to be updated and innovated, with the addition of digital resources, to adapt the teaching and learning processes to students with disabilities. To meet the goal of high‐quality education, teachers must have adequate digital competence to face the educational demands that are placed on them. Therefore, the purposes of this study are: to know the teachers' knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 49 publications
2
48
2
14
Order By: Relevance
“…It has been shown that patterns emphasize collaborative tasks and that the designbased methodology (IBL) is beneficial for the formation of digital teaching competence [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that patterns emphasize collaborative tasks and that the designbased methodology (IBL) is beneficial for the formation of digital teaching competence [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Gros et al [13] points out the link with connectivist theories and sociocultural constructivism, and Gonzalez et al [27] does so with constructivism. In another order, a call to the usual sociocultural approach in the nature of MOOCs is presented in the empirical study dedicated to the level of development of teaching digital competence in [4].…”
Section: Pedagogical Patterns For Tmoocmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Peláez ( 2016 ), Logistic Regression is a multivariate statistical technique that allows estimating the relationship between a dependent variable (digital competence), and a set of independent variables (gender, age, experience and ownership of the center). This analysis technique is the most appropriate to find out if a set of variables explains the level of digital competence of teachers and has been used in other related research (Cabero-Almenara et al, 2021a ; Cabero-Almenara et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…Aun así, también es necesario apuntar distintas limitaciones del estudio como el número de muestra reducida o la especificidad del contexto donde se desarrolla la propuesta formativa. Por ello, sería interesante la replicación del modelo en estudios e investigaciones con la misma o diferente metodología como, por ejemplo, el Scape-Room o la Flipped Clasrroom, puesto que también poseen un alto potencial educativo (Cabero-Almenara et al, 2021a, 2021b, o a través de la incorporación de diferentes tecnologías, sobre todo, a través de las denominadas tecnologías emergentes (Guillén-Gámez et al, 2021;López-Cortes et al, 2021).…”
Section: Discusión Y Conclusiónunclassified